Perbedaan Hasil Belajar Fisika Teknik Mahasiswa Program tudi Pendidikan Teknik Elektro Berdasarkan Latar Belakang Pendidikan dan Jalur Masuk Perkuliahan - Hidayah, Nurul; Usmeldi, Usmeldi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2025)
This study was motivated by the low learning achievement of students in the Engineering Physics course, as evidenced by the fact that there are still students who get an E (failed) in the Engineering Physics course. Students with a vocational high school educational background also tend to have a higher percentage of failures than high school and MA. This study aims to analyze the differences in learning achievement of the Engineering Physics course of students of the Electrical Engineering Education Study Program, Padang State University, class of 2020, based on educational background (SMA, SMK, MA) and college entrance pathways (SNMPTN, SBMPTN, Mandiri). This study uses a quantitative method with a comparative approach. Data were obtained through documentation of students' Engineering Physics course grades, which were analyzed using descriptive and inferential statistical techniques. The results of the study showed that there were significant differences in the learning achievement of the Engineering Physics course of students of the Electrical Engineering Education study program based on educational background. This difference was seen in students with a vocational high school educational background and students with a high school educational background. However, no significant differences were found based on college entrance pathways.